(untitled) (Ius Novum, 2022)
The author of the gloss approves of the Supreme Court’s stance that, provided that in the course of cassation supervision the Supreme Court recognises that the appeal of the party that lodged the cassation had not been upheld and the justification of the appellate court’s judgement flagrantly violates the provision of Article 457 § 3 CPC, and in the cassation, based on the ‘quality’ of this justification, there is a charge of flagrant violation of Article 433 § 2 CPC directly (in the content of the charge) nor in the justification of the cassation (Article 526 § 1 CPC in conjunction with Article 118 § 1 CPC), such a breach requires that the sentence of an appellate court should be overruled because it is required by Article 45 par. 1 Constitution in conjunction with Article 176 § 1 Constitution of the Republic of Poland and the conventional (Article 6 ECHR) standard of a fair appeal trial, which cannot be limited or excluded under Article 537a CPC. This point of view is justified by the fact that the concept of a fair trial as a model of a criminal proceeding means ensuring the minimum level of guarantees for the implementation of the legal state (parties’ rights) and the standard of a fair proceeding is an element of the model of a fair trial. If an appeal proceeding is to be in extenso fair, a court ad quem is obliged to solidly fulfil duties laid down in Article 457 § 3 CPC, i.e. reliably develop a sentence justification, which cannot just include indefinite, general and matching each case statements concerning appropriate establishment of facts and right assessment of evidence, because the above-mentioned phrases that are not connected with the answer to arguments included in an appeal do not provide the appealing party with an actual answer to the issues constituting the basis for formulating charges. Thus, the norm laid down in Article 537a CPC cannot limit or exclude the standard of a fair appeal trial.